Using calculations of the electronically excited states for investigation of fluorescent sensors: A review. Issue 4 (23rd August 2019) - Van Bay, Mai; Hien, Nguyen Khoa; Quy, Phan Tu; Nam, Pham Cam; Van, Dang Ung; Quang, Duong Tuan
Abstract: In this review, the calculations of the electronically excited states were introduced as the recent outstanding applications of quantum chemical calculations for developing the fluorescent sensors. The applications of the ground state and excited state optimized geometry‐based calculations for the absorption and fluorescence properties have been introduced along with their advantages and limitations.